Tracing English Proficiency of Alumni in Supporting Their Career - Farid Noor Romadlon (Universitas PGRI Semarang, 2021)
This study was designed to investigate the English proficiency of Alumni in supporting their career. Sources of data from this study were 802 alumni of Universitas Muria Kudus graduated in 2018 and 115 alumni users who came from companies, government offices, and schools. They filled out a standardized questionnaire from Higher Education Ministry (DIKTI,2017) which was used as an instrument. The results of the analysis show that most alumni regard that English proficiency has much benefit for them to get a job or promoting their career in working place. From skills in English, Speaking becomes the most skill which needed in working place or confirmed by interviewers when alumni have interview test. Furthermore, this study found that alumni users put significant role for foreign language skill (English) of alumni. Users believe that English proficiency of alumni is in good level. However, some users in different working places conclude differently by assessing the alumni English proficiency into Fair category. This can be caused by the kind of working place also affects their English skill, the frequency in using it for working activities, the English atmosphere built by the working place can be an encouragement for alumni to improve their English proficiency. Keywords:Study of Tracing, English Proficiency, Alumni, and Career